Echo Park : [compact disc, unabridged] : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series., 2006)
Detective Harry Bosch, now in the Open-unsolved Unit, receives a call from the DA telling him a serial killer has confessed to several murders. Harry must interview the man about a case he couldn't crack involving the murder of a 22-year-old woman whose body was never found.